Simulación de un sistema eléctrico RC con una fuente de voltaje variable - Romero Pabón, Julio Cesar; Rodríguez Contreras, Jorge Luis; Vergara Ríos, Gabriel Mauricio (Revista MATUA, 2021)
In this research work, the solution of a fundamental application problem in the theory of electrical systems is presented, such as the RC circuit, which contains an electrical resistance, a capacitor and a time-dependent voltage source, its solution contemplates the application of its physical and mathematical foundations, in order to carry out a qualitative and quantitative study that allows obtaining, solving and modeling in Simulink the differential execution and that governs the system.